Empirical patterns of time value decay in options. Issue 4 (22nd September 2017) - McKeon, Ryan
Abstract : Purpose: The purpose of this paper is to conduct an empirical analysis of the pattern of time value decay in listed equity options, considering both call and put options and different moneyness and maturity levels. Design/methodology/approach: The research design is empirical, with great attention paid to creating a standardized measure of time value that can be both tracked over time for an individual option contract and meaningfully compared across two or more different option contracts. Findings: The author finds that moneyness classification at the beginning of the holding period is the key determinant of the pattern of subsequent time decay. The type of option, call or put, and the maturity of the contract have surprisingly little relevance to the pattern of time decay "out-the-money contracts having similar patterns on average, regardless of whether they are calls or puts, 30-day or 60-day contracts." More detailed analysis reveals that In-the-money and out-the-money contracts have slow time decay for most of the contract life, with a significant percentage of the time decay concentrated on the final day of the option. At-the-money contracts experience strong decay early in the life of the option. Research limitations/implications: The study is limited by not having intra-day data included to analyze more frequent price movements. Practical implications: The results reported in the paper provide insight into issues of active management facing options traders, specifically choices such as the initial maturity of the option contract and rollover frequency. Originality/value: Very few studies examine the important issue of how option time value behaves. Time value is the subjective part of the option contract value, and therefore very difficult to predict and understand. This paper provides insight into typical empirical patterns of time value behavior.